“What’s that on your phone?” The aftermath of parents finding sexual and reproductive health messages on their children’s phone in coastal Kenya - Jefferson Mwaisaka; Lianne Gonsalves; Lale Say; Peter Gichangi (Journal of Health and Social Sciences)
Introduction: Digital health interventions allow young people to access information quickly and discreetly, but privacy remains a concern. This article explores what happens when a young user’s privately-access Sexual and Reproductive Health (SRH) messages from a digital health campaign in Kenya are discovered by his/her parents. Methods: This qualitative study took place in Mtwapa, Kenya. Participants were young people aged 15-24 and parents/caregivers of young people aged 15-24. Focus Group Discussions (FGD) with youth (n = 12 FGD, M = 48, F = 49) and caregiver (n = 4 FGD, M =14, F = 19), by using vignettes, explored perceived parental responses about their children accessing SRH information on mobile phones. 97 young people and 33 parent/caregivers participated. Results and Discussion: Sociodemographic characteristics of participants revealed that phone ownership was higher among young men than young women, and particularly low among young women aged 15-17. Youth participants indicated that parents finding SRH messages on their children’s phone would have a range of reactions, from positive to negative: supportive parents would appreciate the messages as a sign their child was being proactive about their health; negative reactions would stem from fear of the message recipient being sexually active. Parent participants accepted children accessing SRH information outside the home as an inevitability, and indicated that parents would cautiously accept or be fully supportive of their child accessing messages on their phone. Conclusions: In the event that a digital health intervention’s young user’s privacy is compromised, these findings demonstrate that the fears of extreme adverse reactions on the part of parents are likely overstated. Specific considerations for future digital health interventions are proposed.